ANALISIS KESALAHAN KESEPADANAN GRAMATIKAL NA’AT-MAN’UT DALAM KARYA AKADEMIK MAHASISWA BAHASA DAN SASTRA ARAB UIN BANDUNG - Agni Nidaulhasanah; Igna Durotunnafisah; Rohanda Rohanda (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze grammatical agreement errors in na‘at-man‘ut structures found in the academic writings of students of Arabic Language and Literature Department at UIN Bandung in 2014. The research focuses on identifying forms of grammatical inconsistencies between adjectives (na‘at) and the nouns they modify (man‘ut) in academic Arabic writing. The research employs a qualitative descriptive method with a linguistic approach, particularly focusing on Arabic syntactic analysis (nahw). The data consist of ten Arabic thesis abstracts, which were collected through documentation techniques by reading, identifying, and classifying erroneous na‘at-man‘ut constructions. The data were analyzed based on classical Arabic grammatical rules and error analysis theory. The findings reveal that the errors primarily involve mismatches in gender (masculine-feminine), number (singular-plural), definiteness (ma‘rifah-nakirah), word category selection, and the use of comparative forms. These errors indicate a lack of mastery of basic syntactic agreement rules in Arabic. This study concludes that na‘at-man‘ut errors in students’ academic texst are systematic and reflect underlying linguistic competence issues. The results are expected to contribute to improving the teaching of Arabic grammar, especially nahwu, in higher education contexts.